COMPLEX BUSINESS SOLUTIONS ON RISK ASSESSMENT AND MANAGEMENT IN RETAIL - V. A. Grosul; T. M. Mkrtchan; S. O. Zubkov; N. N. Karapetyan (Фінансово-кредитна діяльність: проблеми теорії та практики, 2019)
Retail companies are largely addicted to the risk of economic activity due to their industry specifics, which requires them to focus on a comprehensive study of the problem of risk. The purpose of the article is to investigate the operational and financial leverage in terms of using its capabilities to manage the risks of the retail company. The task, the decision of which is aimed at researching this article, is to improve the methodical tools of integrated assessment and risk management in the economic cycle of retail companies in the process of asset conversion. The research of the conditions for the formation of operational and financial leverage in retail companies showed that the calculation of analytical indicators for their assessment has methodological features, due to the structure and nature of used material and financial resources, as well as the formation of effective indicators of economic activity. Under research, it was confirmed the hypothesis of the possibility of comprehensive assessment and risk management of retail companies on the basis of analysis of the variability of profit and the impact on the process of its risks’ generating associated with the use efficiency of assets and capital of the enterprise by calculating the combined effect of the operational and financial leverage. For the reasoned adoption of effective business decisions and ensuring the comprehensiveness of risk assessment and risk management in retail, the proposed methodological approach, which involves the calculation of the cumulative effect of operational and financial leverage, as well as its components, adapted to the specifics of the retail. The research of combined operational and financial risk using the proposed scientific methodological approach has confirmed its effectiveness and correctness of the hypothesis about the need to reflect in the analytical calculations of use in the trade and technological process of retail companies operating lease objects and the value of trade payables.